Enhancing Adolescent Girls' Knowledge about Anemia through Instagram: A Pre-Experimental Study - Zulfajriani Zulfajriani; Nurfatimah Nurfatimah; Christina Entoh; Lisda Widianti Longgupa; Sony Bernike Magdalena Sitorus; Nilda Yulita Siregar; Kadar Ramadhan (Jurnal Bidan Cerdas, 2023)
Introduction: The prevalence of anemia among adolescent girls in Indonesia reaches 32%, necessitating effective measures to improve their knowledge about anemia. The use of Instagram, a social media platform, can be one strategy to provide relevant and important information about anemia. Purpose: To determine the influence of using Instagram as a social media platform on the knowledge of adolescent girls about anemia. Methods: This study employed a pre-experimental design with a one-group pre-test and post-test. A sample of 63 respondents was selected using simple random sampling. The data were analyzed using Paired T-Test and ANOVA. The educational media used on Instagram consisted of short videos and posters. Results: The results of the study revealed that the mean knowledge score of the students before the intervention was 42.4 with a standard deviation of 12.5, while the mean knowledge score after the intervention was 60.1 with a standard deviation of 16.8. There was a significant increase in knowledge by 17.7 points, with a p-value of <0.001, indicating the influence of education through Instagram on the improvement of students' knowledge about anemia. Conclusion: The active use of Instagram as a social media platform plays a crucial role in enhancing the knowledge of adolescent girls about anemia. In the context of health education, Instagram proves to be an effective medium for delivering information to a broader target audience.